2007
DOI: 10.1002/bit.21278
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal effect of cathodic protection on bacterial viability in biofilm attached to carbon steel

Abstract: Biofilm formed on carbon steel by various species of bacterial cells causes serious problems such as corrosion of steel, choking of flow in the pipe, deterioration of the heat-transfer efficiency, and so on. Cathodic protection is known to be a reliable method for protecting carbon steel from corrosion. However, the initial attachment of bacteria to the surface and the effects of cathodic protection on bacterial viability in the biofilm have not been clarified. In this study, cathodic protection was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Alternatively, protective antifouling coatings, such as tributyltin (TBT)-based paints, are used extensively in seawater environments, despite concerns for their toxicity, to combat biofouling and biocorrosion of metallic materials (Jelic-Mrcelic et al, 2006;Yebra et al, 2004). Although cathodic protection has been reported to effectively inhibit biocorrosion of SS by aerobic bacteria (Guezennec, 1994;Miyanaga et al, 2007), it has been found to have no effect on the adhesion of anaerobic bacteria, and is thus unable to prevent the initiation of pitting corrosion by SRB (de Mele et al, 1995). In view of environmental, ecological, and economical impacts, more recent efforts are focused on developing environmentally benign antimicrobial coatings to prevent bacterial adhesion and biofilm formation (AlDarbi et al, 2002;Sreekumari et al, 2005;Telegdi et al, 2005), as the formation of biofilms is widely recognized as the key step in initiating biocorrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, protective antifouling coatings, such as tributyltin (TBT)-based paints, are used extensively in seawater environments, despite concerns for their toxicity, to combat biofouling and biocorrosion of metallic materials (Jelic-Mrcelic et al, 2006;Yebra et al, 2004). Although cathodic protection has been reported to effectively inhibit biocorrosion of SS by aerobic bacteria (Guezennec, 1994;Miyanaga et al, 2007), it has been found to have no effect on the adhesion of anaerobic bacteria, and is thus unable to prevent the initiation of pitting corrosion by SRB (de Mele et al, 1995). In view of environmental, ecological, and economical impacts, more recent efforts are focused on developing environmentally benign antimicrobial coatings to prevent bacterial adhesion and biofilm formation (AlDarbi et al, 2002;Sreekumari et al, 2005;Telegdi et al, 2005), as the formation of biofilms is widely recognized as the key step in initiating biocorrosion.…”
Section: Introductionmentioning
confidence: 99%
“…However, biofilm formation is a big problem when controlling microorganisms in engineering systems. For example, the presence of biofilms on a metal surface as well as the metabolic activities of the biofilm can cause microbiologically influenced corrosion, which can clog the flow in pipes and lead to the deterioration of the heat‐transfer efficiency in oil recovery plants and industrial processes 2–4…”
Section: Introductionmentioning
confidence: 99%
“…Lytic phages from sewage were screened for their specificity for S. aureus , and two phage candidates were shown to control this pathogen in cows with mastitis 9. In addition to S. aureus , other pathogens, like Pseudomonas aeruginosa PAO1, are also being intensively researched as targets for phages 2, 10…”
Section: Introductionmentioning
confidence: 99%
“…14 It is important to mention that the methods listed in Table I correspond roughly to the same number of papers explicitly describing the sterilization procedures in the methodology section of the manuscript. Indeed, most of the papers reviewed do not describe sterilization procedures in enough detail to be reproduced by other laboratories.…”
mentioning
confidence: 99%